2015
DOI: 10.1063/1.4919045
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of three-dimensional helical domain wall in cylindrical NiFe nanowires

Abstract: We report on a micromagnetic study on the dynamics of current-driven helical domain wall (DW) in cylindrical NiFe nanowires. The helical DW is a three-dimensional transition region between magnetizations with clockwise and anticlockwise vortex orientations. A minimum current density is needed to overcome an intrinsic pinning to drive the helical DW, and the propagation along the nanowire is accompanied by a rotational motion. As the driving current strength is increased, the rotation ceases while the DW propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…As depicted by the green isosurface in the snapshots, the BP-DW conical structure begins to deform from one side and completely collapses at t ¼ 0.78 ns. As t ¼ 0.78 ns, no BP is observed, and an unstable 3D transverse-DWlike helical spin structure is formed 53,54 (see the green isosurface in this snapshot). In the process of forming the helical spin structure, it is found that the DW stops moving forward, and the SW formed in front of the DW disappears as well [see the dotted box area in Fig.…”
mentioning
confidence: 92%
“…As depicted by the green isosurface in the snapshots, the BP-DW conical structure begins to deform from one side and completely collapses at t ¼ 0.78 ns. As t ¼ 0.78 ns, no BP is observed, and an unstable 3D transverse-DWlike helical spin structure is formed 53,54 (see the green isosurface in this snapshot). In the process of forming the helical spin structure, it is found that the DW stops moving forward, and the SW formed in front of the DW disappears as well [see the dotted box area in Fig.…”
mentioning
confidence: 92%
“…14 The material parameters used in the simulations correspond to Permalloy (Ni 80 Fe 20 ), i.e., saturation magnetization M s ¼ 860  10 3 A/m, exchange stiffness constant A ex ¼ 1.3  10 À11 J/m, magnetocrystalline anisotropy k ¼ 0, Gilbert damping constant a ¼ 0.005, and non-adiabatic constant b ¼ 0.04-0.15. 8,[15][16][17][18][19] The helical DW dynamics does not show any significant difference for all b values considered. A 350-nm-diameter cylindrical nanowire with a length of 2 lm was used, and a unit cell size of 5 nm  5 nm  5 nm was chosen for all simulations.…”
Section: Methodsmentioning
confidence: 83%
“…As the applied magnetic field is reduced, a clockwise and an anticlockwise vortex are nucleated at the ends of the nanowire, which start to move toward the center of the nanowire, leading to a gradual reduction of the parallel magnetization component that causes a drop in the magnetoresistance (II). At 0 Oe (III), a helical DW 8,9 is found to be nucleated when the two vortices meet at the center of the nanowire. As the magnetic field direction is reversed, the helical DW is annihilated at H % -10 Oe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations